Differences in Comorbidities Between Children and Youth With Suicide Attempts Versus Ideation Presenting to the Emergency Department. Issue 1 (2nd January 2022) - Claudius, Ilene; Axeen, Sarah
Abstract: Objective: The aim of this work was to explore identified risk factors for suicidal ideations and attempts and the differences in these risk factors between emergency department encounters among youth seeking medical care for suicide attempt and those with suicidal ideation. Method: This was a retrospective analysis of suicide-related claims for emergency department visits from nine state-level Healthcare Cost and Utilization Project databases for youth aged 5 through 19 years. Risk factors were estimated by identifying comorbidities recorded in first five diagnosis codes. Odds ratios comparing rates of these comorbidities in encounters for suicide attempts compared to encounters for suicidal ideation were estimated using multivariate logistic regression. Results: In all, 169, 047 encounters for suicide-related behavior were identified. We found higher odds of concurrent anxiety, personality disorders, and alcohol-related diagnoses and lower odds of a comorbid psychosis diagnosis, attention deficit hyperactivity disorder, and other substance-related diagnoses in the population of suicide attempters compared to patients with suicidal ideation alone. Conclusion: The odds of diagnoses of specific comorbidities differed in youth encounters for suicide attempts compared to encounters for suicidal ideation.